Uncovering assets in Brazilian national parks. (1st June 2021) - Bragagnolo, Chiara; Correia, Ricardo A.; Gamarra, Norah Costa; Lessa, Thainá; Jepson, Paul; Malhado, Ana C.M.; Ladle, Richard J.
Abstract: Protected areas (PAs) are the cornerstone of global conservation policy and have expanded dramatically over the last century. Though unequivocally beneficial for biodiversity, gazetting land for protecting nature can also be seen as an 'opportunity cost' that some politicians are unwilling to pay. One of the most effective strategies to increase the political resilience of PAs in the face of such threats is to demonstrate their broader value to society. This is one of the objectives of the recently proposed 'PA asset framework'. The framework conceptualizes PAs as being composed of suites of biophysical, human, infrastructure, institutional and cultural assets that interact with individuals and institutions to generate different forms of tangible and intangible value. Here, we test the utility of the framework by conducting an asset-based analysis of Brazilian National Parks (NPs) at two different scales (NP system and NP unit). Assets were identified at the system level through a systematic review of 49 Management Plans (MPs) using a typology of PA asset classes as a tool for characterising the presence and state of assets in or associated with NPs. At the NP unit level, assets were identified through semi-structured interviews with local managers of the Chapada Diamantina National Park. Biophysical and infrastructure assets were the most represented asset classes at both scales. Our analysis successfully revealed: (i) which assets can be managed to generate wider forms of values at local scale (e.g. natural spectacles, iconic species, park volunteers) (ii) relational values between assets (e.g. trails and outdoor recreational features), and (iii) value generating practices (VGPs) to capture values from the interaction between different assets (i.e. restoration of degraded areas through voluntary programmes, etc.). We conclude by discussing how the PA asset framework can be operatively integrated into NP management to improve the future allocation of limited financial resources. Highlights: Protected Area Asset Framework re-conceptualizes PAs as a spatial asset class. We adopted the Framework to explore assets in Brazilian National Parks. Outcomes combine contents of management plans and viewpoint of park managers. Cultural and social assets are poorly recognized at both local and federal scales. Integrating asset-based analysis in PA management can enhance resource allocation.